Streptococcal periorbital necrotizing fasciitis: Case series on a rare but potentially life-threatening entity - Isabella D. Baur; Isabel Habert; Monica Markstaller; Kathrin Hartmann; Arthur Mueller (Heliyon)
Objective: Periorbital necrotizing soft tissue infection (NSTI) is a rare entity caused either by polymicrobial infection (type 1) or Streptococcus pyogenes and/or Staphylococcus species (type 2). A high level of clinical suspicion is necessary to make the diagnosis. We present 3 cases of NSTI illustrating our diagnostic and therapeutic approach. Patients and methods: The main outcome measures were laboratory and clinical findings at initial presentation, microorganism cultured, predisposing conditions and the number of debridements needed as well as final outcomes. Results: Biomarkers of inflammation in blood samples were elevated at admission and Streptococcus pyogenes was cultured in all three cases. Clinical suspicion of this rare disease and prompt surgical treatment was crucial to confirm the diagnosis.Imaging and laboratory workup, however, did not prove to be diagnostically helpful in our cases. We performed early and consequent debridement of necrotic tissue to control the infection alongside adequate systemic antibiotic therapy including clindamycin in all cases of suspected NSTI. As intraoperative findings revealed necrotic tissue even in an apparently quiet situs, we decided to debride the wound daily after the first surgery until there is very little or no necrotic tissue to debride seen intraoperatively. Conclusions: Based on the negative experience with our first case, we developed a more aggressive surgical plan for cases with periorbital NSTI. After early debridement, the patient is surgically reevaluated on a daily basis until surgery is deemed to have been unnecessary. We follow this approach, as necrotic tissue is sometimes identified intraoperatively from a lack of resistance to manipulation rather than from its clinical aspect alone. At a later point, plastic surgery may be required when the infection is under control.